Software Optimization of Welding Machine Motion System Based on Switch Control Algorithm - Yin, Jingbo; Liu, Xing; Guo, Xunde; Gudsla, Lianwang (Mobile information systems, 2022)
In order to improve the software optimization of welding machine motion system based on switch control algorithm. Based on soft switch arc welding power source current peak control the stability of the BUCK converter, the method by solving peak current control circuit transfer function, and to analyze the formation mechanism of soft switch arc welding power source external characteristic, the frequency of pulse current in the simulation model is set to 200 Hz, the base value of pulse current is 40 A, the peak value of pulse current is 500 A, and the duty cycle is 40%. The welding wire melting speed during the peak value of pulse current is 480 mm/s, while the base value of pulse current is 20 mm/s. The results show that in the 2 s moment of the simulation model, the welding torch suddenly drops from 40 mm height to 30 mm height. Inevitably, the arc length changes from about 16 mm before the step to about 6 mm, which is basically equal to the step change distance. Using pulse frequency modulation (PFM) and adaptive adjustment of pulse current related parameters, effectively eliminate the interference factors in the welding process, quickly adjust arc welding parameters to make the welding wire melting speed equal to the wire feeding speed, maintain the stability of the welding process, and improve the weld forming effect. It is of great significance to the software optimization of the motion system of the pulse welding machine.